2017
DOI: 10.1109/toh.2016.2582485
|View full text |Cite
|
Sign up to set email alerts
|

Vibrotactile Sensitivity in Active Touch: Effect of Pressing Force

Abstract: An experiment was conducted to study the effects of force produced by active touch on vibrotactile perceptual thresholds. The task consisted in pressing the fingertip against a flat rigid surface that provided either sinusoidal or broadband vibration. Three force levels were considered, ranging from light touch to hard press. Finger contact areas were measured during the experiment, showing positive correlation with the respective applied forces. Significant effects on thresholds were found for vibration type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 35 publications
2
36
2
2
Order By: Relevance
“…That might also contribute to explain the generally lower thresholds that we found for higher forces. In our study, force level was found strongly correlated to contact area, resulting in larger areas for higher forces, which clearly contributed to further lowering perceptual thresholds [43].…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…That might also contribute to explain the generally lower thresholds that we found for higher forces. In our study, force level was found strongly correlated to contact area, resulting in larger areas for higher forces, which clearly contributed to further lowering perceptual thresholds [43].…”
Section: Discussionsupporting
confidence: 51%
“…Intuitively, a reason for that is that the number of stimulated skin receptors increases with larger contact areas. In the present experiment, the interactive nature of the task resulted in high variability of the contact area [43]. The mean contact areas measured in the experiment were in the range 103-175 mm 2 , contributing to explaining the reported enhanced sensitivity.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…In addition, the knowledge gained from the psychophysical studies performed after discrimination experiments can be used for the design of better haptic interfaces. During the design of haptic systems for virtual environment, it is important to consider the resolution of the haptic display to that of the human sensory systems (Tan et al, 1993;Wurdemann et al, 2013;Papetti et al, 2017).…”
Section: Stiffness Discriminationmentioning
confidence: 99%
“…An early prototype was used to study how auditory, tactile, and audio-tactile feedback affect the accuracy of finger pressing force [18]. A [33] more recent psychophysical experiment-described in Sect. 4.2 and making use of a more advanced prototype, described below-investigated how vibrotactile sensitivity is influenced by actively applied finger pressing forces of various intensities.…”
Section: The Touch-boxmentioning
confidence: 99%